2023
DOI: 10.3389/fpubh.2023.1006527
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the identification of related factors and preventive strategies of hip fracture

Abstract: Hip fracture is the most devastating type of osteoporosis-related fracture, and is a major worldwide public health problem with a high socioeconomic burden, morbidity rate, and mortality rate. Thus, it is crucial to uncover the risk factors and protective factors to create a hip fracture prevention strategy. In addition to a briefly review of some well accepted risk and protective factors of hip fracture, this review mainly summarized the recent advances in the identification of emerging risk or protective fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 152 publications
2
2
0
Order By: Relevance
“…Similarly to the results of this research, some studies indicated that the development of society and growing wealth in certain areas across the world is followed by changes in trends in rates of incidence of and YLDs from hip fractures due to falls, suggesting that economic prosperity is of great importance for the magnitude and direction of trends of hip fracture [9,24,42]. With the prosperity of society comes better acute care and increased availability of improved therapeutic modalities and preventive strategies, which results in an increase in the number of elderly people who survive after hip fractures due to falls, a significant percentage of whom require long-term care due to various degrees of disability [5,42,43].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similarly to the results of this research, some studies indicated that the development of society and growing wealth in certain areas across the world is followed by changes in trends in rates of incidence of and YLDs from hip fractures due to falls, suggesting that economic prosperity is of great importance for the magnitude and direction of trends of hip fracture [9,24,42]. With the prosperity of society comes better acute care and increased availability of improved therapeutic modalities and preventive strategies, which results in an increase in the number of elderly people who survive after hip fractures due to falls, a significant percentage of whom require long-term care due to various degrees of disability [5,42,43].…”
Section: Discussionsupporting
confidence: 75%
“…Similarly to the results of this research, some studies indicated that the development of society and growing wealth in certain areas across the world is followed by changes in trends in rates of incidence of and YLDs from hip fractures due to falls, suggesting that economic prosperity is of great importance for the magnitude and direction of trends of hip fracture [9,24,42]. With the prosperity of society comes better acute care and increased availability of improved therapeutic modalities and preventive strategies, which results in an increase in the number of elderly people who survive after hip fractures due to falls, a significant percentage of whom require long-term care due to various degrees of disability [5,42,43]. In this study, the Human Development Index inversely correlated with rates of YLDs from hip fractures due to falls, suggesting that people in areas with a prosperous social economy and well-being are more likely to be aware of issues concerning hip fractures due to falls, to have a healthy lifestyle, and to have access to higher levels of health care services, which would be beneficial to the prevention and management of hip fractures.…”
Section: Discussionsupporting
confidence: 75%
“…These fractures are primarily caused by low-energy trauma, often resulting from falls, while the root causes are age-related factors such as impaired balance, muscle weakness, and decreased bone mineral density [ 2 ]. Geriatric hip fractures are associated with high morbidity and mortality rates [ 3 ], primarily due to pre-existing comorbidities, surgical complications, and postoperative immobility [ 4 ]. Common complications include surgical site infections, urinary tract infections, venous thromboembolism, pressure ulcers, pneumonia, and delirium.…”
Section: Introductionmentioning
confidence: 99%
“…26 Bone regeneration ability was one of the major factors for the rehabilitation of geriatric hip fractures: patients with strong bone regeneration abilities can get out of bed and exercise more quickly, reducing their bedridden time and consequently decreasing the risk of postoperative complications such as blood clots, pneumonia, and bedsores. 27,28 As a result, they have a better prognosis. The LDL-c may relate to the mortality and walking ability of hip fractures by influencing bone metabolism.…”
mentioning
confidence: 99%